An Ecological-Oriented Policy Development Framework as An Alternative to Contesting Land-Oriented and Maritime-Oriented Paradigms - Rahmawati, Deti (Department of Government, FISIP, Universitas Padjadjaran, 2021)
Two diverging geography-oriented Policy development paradigms have been prevailing within the discourse of Indonesian context, namely land and maritime-oriented paradigms. The two paradigms often emerge in ideological discourses that predispose national identity. Throughout the Indonesia’s history, discourses on development paradigms seems to alternate between two paradigms. However, since 2014, maritime paradigm has taken a dominant role in the Indonesian discourses.This paper propose empirical data associated with the environmental, economic and social conditions of Segara Anakan, Central of Java, we show how the land paradigm has resulted in undesirable consequences. Segara Anakan is a coastal region in which various communities have for decades developed economic activities. Major environmental damages in the region have been reported and social conflicts have occurred unresolved. Instead of choosing between land and maritime paradigms, in this paper we propose a more ecological-oriented development framework that is based on actor-network theory. we emphasis key measures: registering relevant heterogeneous entities, including human actors, social groups, small islands, straits, ocean inhabitants, etc; consultations that involve various spoke-persons. We argue in the paper that both land and maritime paradigms are too macro in their scope to tackle heterogeneities and complexities at the regional scopes.